Reactive oxygen species and extracellular signal-regulated kinase 1/2 mediate hexachlorobenzene-induced cell death in FRTL-5 rat throyd cells - Chiappini, Florencia Ana (2013)
Hexachlorobenzene (HCB) is an organochlorine pesticide widely distributed in the environment. We have previously shown that chronic HCB exposure triggers apoptosis in rat thyroid follicular cells. This study was carried out to investigate the molecular mechanism by which the pesticide causes apoptosis in FRTL-5 rat thyroid cells exposed to HCB (0.005, 0.05, 0.5, and 5μM) for 2, 6, 8, 24, and 48 h. HCB treatment lowered cell viability and induced apoptotic cell death in a dose- and time-dependent manner, as demonstrated by morphological nuclear changes and the increase of DNA fragmentation. The pesticide increased activation of caspases- 3, -8, and full-length caspase-10 processing. HCB induced mitochondrial membrane depolarization, release of cytochrome c and apoptosis-inducing factor (AIF), from the mitochondria to the cytosol, and AIF nuclear translocation. Cell death was accompanied by an increase in reactive oxygen species (ROS) generation. Blocking of ROS production, with a radical scavenger (Trolox), resulted in inhibition of AIF nuclear translocation and returned cells survival to control levels, demonstrating that ROS are critical mediators of HCB-induced apoptosis. The pesticide increased ERK1/2, JNK, and p38 phosphorylation in a timeand dose-dependent manner. However, when FRTL-5 cells were treated with specific MAPK inhibitors, only blockade of MEK1/2 with PD98059 prevented cell loss of viability, as well as caspase-3 activation. In addition, we demonstrated that HCB-induced production of ROS has a critical role in ERK1/2 activation. These results demonstrate for the first time that HCB induces apoptosis in FRTL-5 cells, by ROS-mediated ERK1/2 activation, through caspase-dependent and -independent pathways.